Zinc oxide (ZnO) induced toxicity and behavioural changes to oligochaete worm Tubifex tubifex (Muller) - Chatterjee, Arnab; Bhattacharya, Ritwick; Saha, Nimai Chandra (International Journal of Scientific Research in Biological Sciences, 2019)
Zinc is among the important trace element of the body by participating in several biological processes. But it shows toxicity after a certain concentration. Zinc oxide (ZnO), a hazardous heavy metal, is frequently used in both bulk and nanoparticle format in industrial and household purposes throughout India. In the present study the 24, 48, 72 and 96h LC50 values of ZnO was monitored to benthic oligochaete worm Tubifex tubifex (Muller) through Finney’s probit analysis method. Different abnormal behavioural changes in the worm were also recorded during the exposure period. The 24, 48, 72 and 96h LC50 values of Zinc oxide (ZnO) to Tubifex tubifex was obtained as 30.88, 24.15, 19.95 and 11.15 mg/l respectively. The mortality rate of Tubifex tubifex varied significantly (p<0.05) with a dose and time dependent manner (24, 48, 72 and 96 h). The exposed worm showed several erratic behaviors with the gradually increasing concentrations of the metal and with the progress of time of exposure. The safe concentration of this metal was ranged between 0.0001115 -1.11 mg/l. Based on 96h LC50 value the Maximum allowable concentration (MAC), no observable effect concentration (NOEC) and the lowest observable effect concentration (LOEC) of Zinc oxide to Tubifex tubifex were 1.11, 1.3 and 2.1 mg/l respectively. The present study will be useful in determination of the safe dose of the toxicant before its disposal to the environment.